The mandibular rehabilitation multidisciplinary after mandibulectomy (Research, Society and Development, 2022)
Current treatment of odontogenic tumors (OT) ranges from simple enucleation by curettage or segmental resection. But the treatment does not stop here, we need to think about the rehabilitation of the patients. The Mandibular reconstruction can begin immediately postoperatively, but the delayed reconstruction can be the best option for treatment, because of the high risk of recurrence in some OT, but it is always a challenge. The aim of this study is to describe the approach of a case of mandibular odontogenic myxoma and your total rehabilitations. The segmental hemi-mandibulectomia was performed with an intraoral. After 2 year the iliac crest grafting to intraoral approach was done and after 6 months osseointegrated implants were put and the immediate load with hybrid prostheses was done. After 2 years of complete rehabilitation we can consider that this sequence looks like to be a good form to become social, psychological, esthetic and function in the patients.